TRANSCENDING POSTMODERNISM performatism 2.0. - Eshelman, Raoul, 1956- ([S.l.] : ROUTLEDGE, 2025)
Transcending Postmodernism: Performatism 2.0 is an ambitious attempt to expand and deepen the theory of performatism. Its main thesis is that, beginning in the mid-1990s, the strategies and norms of postmodernism have been displaced by ones that force readers or viewers to experience effects of aesthetically mediated transcendence. These effects include specific temporal strategies (chunking), stylizing separated subjectivity (the genius and the fool being its two main poles) and orienting ethics toward actions taken by centered agents bearing a sacral charge. The book provides a critical overview of other theories of post-postmodernism, and suggests that among five text-oriented theories there is basic agreement on its techniques and strategies.
Keywords: Transcendence (Philosophy); Postmodernism